The Effect of Pre-Pregnancy Classes on Hemoglobin Levels in Prospective Brides and Grooms in the Ciruas Community Health Center Work Area, Serang Regency, Banten Province - Eti Herawati; Rukmaini; Rosmawaty Lubis (Rajaki of Tulip Medika Publisher, 2025)
Anemia in women of reproductive age remains a health problem that impacts pregnancy. Promotional efforts through pre-pregnancy classes are expected to improve hemoglobin levels, knowledge, and eating patterns of expectant mothers. The purpose of this study was to analyze the effectiveness of pre-pregnancy classes on hemoglobin levels, knowledge, and eating patterns. The study used a quasi-experimental design with an intervention and control group. The majority of respondents were aged 21–30 years (78.7%), had a college education (45.0%), had sufficient knowledge (41.3%), and had sufficient eating patterns (37.5%). The results showed a significant difference in hemoglobin levels before and after the class in the intervention group (p=0.005; t=-16.09) and the control group (p=0.006; t=-1.9). There was no difference in hemoglobin levels between the two groups before the intervention (p = 0.37), but a significant difference emerged after the intervention (p = 0.005; t = -13.39). There was no significant relationship between knowledge and hemoglobin levels (p=0.37) or eating patterns with hemoglobin levels (p=0.53) before the intervention. There was a significant difference in knowledge before and after the class in the intervention group (p=0.005; t=-4.197) and the control group (p=0.006; t=-5.231). The difference in knowledge between groups was only apparent after the intervention (p=0.005). Eating patterns showed a significant difference before and after the class in the intervention group (p=0.005; t=-9.581), but did not differ significantly between groups after the intervention (p=0.843). Pre-pregnancy classes were effective in improving hemoglobin levels, knowledge, and eating patterns of expectant mothers, although the direct relationship between knowledge and eating patterns and hemoglobin levels was not significant.